2019
DOI: 10.1002/jbio.201800466
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the murine skull on high‐frequency transcranial photoacoustic brain imaging

Abstract: Non‐invasive photoacoustic tomography (PAT) of mouse brains with intact skulls has been a challenge due to the skull's strong acoustic attenuation, aberration, and reverberation, especially in the high‐frequency range (>15 MHz). In this paper, we systematically investigated the impacts of the murine skull on the photoacoustic wave propagation and on the PAT image reconstruction. We studied the photoacoustic acoustic wave aberration due to the acoustic impedance mismatch at the skull boundaries and the mode con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 54 publications
(63 reference statements)
1
17
0
Order By: Relevance
“…The cross-sectional profiles of four selected vessels (azPA, RRV, AchA, and LSCA) are co-plotted with their corresponding control group in different line types (Figure 4D). Obviously, the vessel signal of the skull-removed mouse was about four times stronger than that of the normal mouse, which is consistent with an earlier theoretical prediction (Liang et al, 2019).…”
Section: Pact Imaging Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The cross-sectional profiles of four selected vessels (azPA, RRV, AchA, and LSCA) are co-plotted with their corresponding control group in different line types (Figure 4D). Obviously, the vessel signal of the skull-removed mouse was about four times stronger than that of the normal mouse, which is consistent with an earlier theoretical prediction (Liang et al, 2019).…”
Section: Pact Imaging Resultssupporting
confidence: 91%
“…Kneipp et al, estimated the skull insertion loss using a photoacoustic point source and found good quantitative agreement between their model and measurements (Oraevsky et al, 2016). Yao et al (2015) investigated the evolution of the acoustic waveform when penetrating through the skull (Liang et al, 2019). Acoustic ray-tracing was used to calculate the phase distortion along the acoustic travel path, and compensation algorithms were developed based on vector space similarity model and ray-tracing simulations (Mohammadi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These disadvantages complicate accurate image reconstruction. Yao's group systematically investigated the impact of murine skull on PA wave propagation and the corresponding PAI image reconstruction [83]. Their results confirmed that transcranial PACT displayed an inferior image quality compared with transcranial PAM (seen Figure 5), even in instances where the two modalities use a similar US frequency and effective detection aperture.…”
Section: Pai In Combination With Other Imaging Techniquesmentioning
confidence: 84%
“…In the NIR I range, light scattering, hemoglobin absorbance, and skull attenuation interferes in the signal/noise ratio, unmixing, and penetration depth in the small animal brain ( Wan et al, 2018 ; Liang et al, 2019 ). The skull attenuation positively associates with increasing age, which makes imaging in aged disease animal models difficult.…”
Section: Hybrid Contrast Agents For Multimodal Oa Brain Imagingmentioning
confidence: 99%